ISSUES OF UKRAINIAN INDUSTRIAL ENTERPRISES’ INNOVATION DEVELOPMENT - Г. В. Карпінська (Ринкова економіка: сучасна теорія і практика управління)
The article considers the position of Ukrainian economy in global economy according to the rankings Global Competitiveness Index World Economic Forum and its innovation component. The state of science, technology and innovation in Ukraine is analyzed. It was determined that the level of innovation activity, production of high-tech products, funding science in Ukraine is far behind the leading countries. The main problems that hinder the innovative development of industrial enterprises of Ukraine are the problems of funding and inefficient state innovation policy, leading to the reduction and outflow as highly skilled experts and the results of their research. It was found that the solution of these problems lies primarily in the activation of state support of innovation activity through the creation of an effective system of mechanisms and incentives for innovation, improvement the state of intellectual property rights’ protection and research commercialization.